S76 Endoplasmic reticulum stress correlates with fibrosis in interstitial lung disease. (15th November 2016) - Parfrey, H; Moseley, E; Beardsley, B; Knight, J; Marciniak, SJ; Rassl, D
Abstract : In interstitial lung disease (ILD), pulmonary fibrosis is associated with a poor prognosis. Distinct histological features differentiate between the ILDs, however it is unknown if there are shared pathogenic mechanisms for the development of fibrosis. Endoplasmic reticulum (ER) stress has been implicated in the pathogenesis of familial and sporadic idiopathic pulmonary fibrosis (IPF). In response to ER stress, cells trigger the integrated stress response and upregulate chaperones, such as BiP, and the phosphatase GADD34, which can regulate EMT, cell proliferation and survival. AIMS: We hypothesise that ER stress may be involved in the pathogenesis of fibrosis in all interstitial lung diseases. Paraffin embedded lung biopsy sections from 8 patients with familial pulmonary fibrosis, 11 sporadic idiopathic pulmonary fibrosis (IPF), 12 non-specific interstitial pneumonia (NSIP) and 10 hypersensitivity pneumonitis (HP) were evaluated for BiP and GADD34 by immunohistochemistry. Using light microscopy, 6 high power fields were scored for fibrosis, inflammation, BiP and GADD34 using semi-quantitative analysis by 2 blinded, independent investigators. Data were analysed by linear regression using Prism software. BiP and GADD34 were localised to reactive type II pneumocytes and columnar epithelium within areas of fibrosis. GADD34 was also evident in the endothelium. No staining was detected in fibroblasts. Epithelial GADD34 correlated with extent of fibrosis in familial pulmonary fibrosis (r 2 = 0.72, p < 0.001), IPF (r 2 = 0.51, p < 0.0001) and NSIP (r 2 = 0.46, p < 0.0001). In contrast, BiP was associated with fibrosis in IPF (r 2 = 0.49, p < 0.0001) and HP (r 2 = 0.59, p < 0.0001). These data show that ER stress and the unfolded protein response are associated with fibrosis in ILD. Hence targeting ER stress may be a novel therapeutic option for pulmonary fibrosis.